How does camphor tree affect the wind and pollutants in the street canyon:a novel CFD method based on a point cloud algorithm? - Le Wang; Xilian Luo; Qingyi Wang; Liyu Tang; Zhaolin Gu; Shiyu Duan; Zeyi Li (Trees, Forests and People, 2025)
This study investigates the impact of camphor trees on airflow and pollutant dispersion in street canyons. As innovative research, it utilizes three-dimensional point cloud measurement data to extract and reconstruct tree TB (trunk and branches), establishing a mathematical model for the resistance source term that accurately describes the external morphology of the tree crown and the discontinuous, non-uniform characteristics of the internal leaves. This method addresses the challenges associated with accurately characterizing tree features. Based on this novel methodology, numerical simulations were conducted to investigate the effects of various tree characteristics and layouts on the wind environment and pollutant distribution in street canyons. The results indicated that the irregular distribution of camphor tree TB and crowns leads to significant differences in airflow patterns, flow velocities, and pollutant concentration across different cross sections of the street canyon. Whether only camphor tree TB or whole camphor trees (including crowns and TB) are present, neglecting the influence of tree TB results in an overestimation of the average airflow velocity and an underestimation of the average pollutant concentration at the canyon's bottom. This effect is particularly pronounced in areas with only tree TB, leading to a 14 % reduction in average airflow velocity. The obstruction effect of TB on airflow is diminished by the resistance effect of leaves. Furthermore, when considering the influence of camphor tree crown layout, the crown positioned in the middle of the street canyon has the most significant impact on airflow dynamics. The crown near the leeward side effectively increases airflow velocity and significantly reduces pollutant concentration at the bottom compared to the crown near the windward side.